Response of Nicotiana tabacum grown under Pb stress: A preliminary study - Phang, Ing Chia; Razak, Nurhayati; Ismail, Nor Adibah; Pappusamy, Arokiaraj (2012)
Heavy metal contaminations in soil, water and air has become a major problem since the onset the industrial revolution. Among the heavy metals that are being studied, lead (Pb) is one of the highly persistent and widely distributed in the environment. This heavy metal contaminant can be transferred into the food chain, causing the bioaccumulation of heavy metals in the organism tissues, and thus affecting public health. Phytoremediation emerges as a remediation tool based plant to clean up heavy metal contaminated sites. Hence, a better understanding of the physiological, biochemical and molecular responses in plant could facilitate the success of this plant-based technology. Nicotiana tabacum is used in the present study because it poses the important characteristics to study gene expression in plants. Furthermore, it is repulsive to herbivores, and thus minimizes the possibility of Pb from entering food chain. In this preliminary study, the physiological response of N.tabacum exposed to Pb was investigated in a laboratory condition. The growth and morphological changes of Pb-treated N.tabacum were compared with those without Pb treatment (control). Pb concentrations of up to 2.0 mM were used and symptoms of Pb toxicity were observed.